Technology Literacy and Religious Interest of Madrasah Ibtidaiyah Teacher Education (PGMI) Program Students / Literasi Teknologi dan Peminatan Keagamaan Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah - Salamah, Umi; Makhrus, Ali; Munir, Misbahul; Said, Akhmad (STAI Ma'had Aly Al-Hikam Malang, 2021)
The rapid development of technology demanded young generations to continue adapting to new cultures. This study was aimed to describe students' technology- literacy, students’ interest in social media, and preferred religious figures in online religious studies. This research was a qualitative study using a case study design. The data were collected through observation and interviews with the students of Madrasah Ibtidaiyah Teacher Education (PGMI) program in STAI Ma'had Aly Al-Hikam Malang chosen randomly. The result showed that the students’ technology literacy skills were quite good. They had a capacity to use social media optimally, integrative, and instrumentally. Furthermore, the religious figures admired by the students were diverse and came from multicultural.